(untitled) (Third Sector Social Economic Review, 2023)
This research was conducted to determine the effects of context-based learning approach in Social Studies Curriculum and social studies textbooks. In the research, 4th, 5th, 6th and 7th grade social studies textbooks, which were accepted as textbooks to be taught in public schools in the 2021-2022 academic year, by the decision of the Ministry of National Education, Board of Education and Discipline were examined. For this purpose, the document analysis method, one of the qualitative research methods, was used in the research. In the data analysis phase of the research, descriptive analysis technique was used. As a result of the research, it was determined that there are 131 acquisitions in all grade levels in the Social Studies Curriculum, 92 of these acquisitions are suitable for the context-based approach. In addition, in the examination of whether the acquisitions that are suitable for the context-based approach include a context-based element in the textbooks, it was determined that 57 out of 92 acquisitions contain context-based elements. When the total number of achievements in the Social Studies Curriculum is examined, it is concluded that this rate is low. In line with the results obtained from the research; ""Context-based elements should also be included in the textbooks in accordance with the acquisitions that include context-based elements in the Social Studies Curriculum."" It has been seen that it is suitable for the context-based approach. For this, the context-based teaching approach should be used more effectively in the social studies course."" and ""Experimental studies can be planned to compare the social studies course conducted on the basis of the context-based approach and the traditional social studies course in terms of success, attitude, interest and motivation."" recommendations are presented.